2012
DOI: 10.1093/rheumatology/ker446
|View full text |Cite
|
Sign up to set email alerts
|

PTPN22 R620W polymorphism in the ANCA-associated vasculitides

Abstract: The PTPN22 620W allele confers susceptibility to the development of GPA (but not of MPA or CSS), and particularly of its ANCA-positive subset.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 46 publications
4
45
0
Order By: Relevance
“…The extensive Botnia study did not confirm the association of c.1858C>T polymorphism with T1DM, but did support the association of c.1858C>T with the expression of GADA with an OR of 1.6 (95% CI 1.2-2.2) [52]. Similarly, the T allele is associated with the presence of anticitrullinated α-enolase peptide-1 autoantibodies (but not anticitrullinated vimentin peptide 60-75 or the anticyclic citrullinated peptide autoantibodies) in rheumatoid arthritis [53] and ANCA in ANCA disease [17,18]. In contrast to the above findings, Gabbay et al [54] did not find any association of the c.1858C>T polymorphism with GADA or IA-2A levels in T1DM patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The extensive Botnia study did not confirm the association of c.1858C>T polymorphism with T1DM, but did support the association of c.1858C>T with the expression of GADA with an OR of 1.6 (95% CI 1.2-2.2) [52]. Similarly, the T allele is associated with the presence of anticitrullinated α-enolase peptide-1 autoantibodies (but not anticitrullinated vimentin peptide 60-75 or the anticyclic citrullinated peptide autoantibodies) in rheumatoid arthritis [53] and ANCA in ANCA disease [17,18]. In contrast to the above findings, Gabbay et al [54] did not find any association of the c.1858C>T polymorphism with GADA or IA-2A levels in T1DM patients.…”
Section: Discussionmentioning
confidence: 99%
“…The single nucleotide polymorphisms (SNPs) of PTPN22 , predominantly p.Arg620Trp (c.1858C>T), are among the major causative agents of human autoimmune disorders. Associations of PTPN22 SNPs with type 1 diabetes (T1DM) [3,4,5], latent autoimmune diabetes in adults (LADA) [6,7], autoimmune thyroid diseases (including Graves' disease and Hashimoto's thyroiditis) [8,9,10], rheumatoid arthritis (including anticitrullinated peptide antibody-negative subjects) [11], juvenile idiopathic arthritis [12], systemic lupus erythematosus [13,14,15], thymoma-associated myasthenia gravis [16], antineutrophil cytoplasmic autoantibodies (ANCA) disease [17,18], vasculitis (including ANCA-associated vasculitis, Wegener's granulomatosis and Behçet's disease) [19], chronic spontaneous autoreactive urticaria [20], and generalized vitiligo [21,22,23] have repeatedly been reported. PTPN22 polymorphisms also affect the responses of chronic-phase chronic myeloid leukemia patients to treatment with the tyrosine kinase inhibitor imatinib [24].…”
Section: Introductionmentioning
confidence: 99%
“…Deficiency of α 1 -antitrypsin has been shown to correlate with PR3-ANCA positive vasculitis, and the PiZ allele has been found to be associated with a more severe disease and worse prognosis [9]. An association between a polymorphism in PTPN22 have been reported in AAV [10] and in ANCA positive GPA [11,12]. A genomewide association study (GWAS) showed associations between AAV and a number of single-nucleotide polymorphisms following ANCA specificity rather than the clinical syndromes.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the group of patients with ANCA-negative EGPA was associated with the haplotype IL10.2 of the IL-10 promoter polymorphism, functionally resulting in an increase expression of IL-10 [22]. Other nucleotide polymorphisms have shown little or no effect on EGPA susceptibility [23][24][25].…”
Section: Genetic and Environmental Factorsmentioning
confidence: 99%